Apostolic Networks in the Third Wave of the Spirit: John Wimber and the Vineyard - Bialecki, Jon (Pneuma, 2016)
This essay discusses the relationship between the Vineyard and the various other apostolic networks. By comparing the Vineyard with C. Peter Wagner and the New Apostolic Revival, I contend that the chief difference between these two movements lies in a Vineyard interest in pedagogy over a New Apostolic Revival interest in governance, and in the Vineyard’s use of the figure of John Wimber as an exemplar for practice rather than as a figure of authority.